Von verteiltem zu geteiltem Wissen: Konzeption und Durchführung eines semivirtuellen Seminars zur Mathematikdidaktik (mathematica didactica, 2004)
The seminar „space geometry“ was taught combining different classes at four different universities. The main idea was to build a semi-virtual seminar with collaborating groups of distributed expertise. Their task was to specify mathematic standards in space geometry while creating a matching website, and to prepare a face-to-face presentation of the groups’ seminar work. This report describes the goals, principles and assignments of the seminar, the methodology used and some results of the accompanying research study.